Performing the Rural in Contemporary Irish Theatre. (November 2019) - Collins, Christopher
Abstract : In this article Christopher Collins considers how the rural is represented in contemporary Irish theatre through a performance analysis of WillFredd Theatre's award-winning production of FARM, staged in an industrial Dublin warehouse. Adopting a relational perspective, the article explores how the rural in contemporary Irish culture is a valuable commodity that is produced for urban consumption, and examines how the representation of the rural in FARM offered a critique of economies of capital that obscure the inherent labour of producing the rural. It also highlights how the performance explored the workings of the Irish cultural economy that produces rural nostalgia as an affective practice at the expense of some of the lived realities of rural life that extend beyond labour to loneliness, depression, and gendered essentialism. Consequently, Collins questions what, if anything, has changed from the representation and reception of the rural as nostalgic utopia, and the role nostalgia plays in articulating regional and national identities. Christopher Collins is an Assistant Professor of Drama at the University of Nottingham. He has published widely on modern and contemporary Irish theatre, including two monographs on the plays and performances of J. M. Synge. In 2016 he was appointed as Secretary General (Communications) for the International Federation for Theatre Research.